MARKETING EKOTIZIMINI BOSHQARISH VA MUVOFIQLASHTIRISH MEXANIZMLARINI TAKOMILLASHTIRISH YOʻNALISHLARI - Sobirov Azizbek Avazbekovich (MANAGEMENT AND ECONOMICS SCIENTIFIC RESEARCH JOURNAL, 2025)
This article explores the directions for improving the mechanisms of management and coordination in marketing ecosystems from a scientific perspective. The study analyzes the modern structure of marketing ecosystems under digital transformation, coordination methods among stakeholders, and the integration of artificial intelligence technologies. Based on empirical data, effective models for managing marketing ecosystems and the impact of omnichannel strategies on customer experience are evaluated. The findings provided an opportunity to develop practical recommendations for companies.